Voices of Labor: Creativity, Craft, and Conflict in Global Hollywood - Curtin, Michael (University of California Press, 2017)
Motion pictures are made, not mass produced, requiring a remarkable collection of skills, self-discipline, and sociality-all of which are sources of enormous pride among Hollywood's craft and creative workers. The interviews collected here showcase the pleasures that attract people to careers in film and television. They also reflect critically on changes in the workplace brought about by corporate conglomeration and globalization. Rather than offer publicity-friendly anecdotes by marquee celebrities, Voices of Labor presents off-screen observations about the everyday realities of Global Hollywood. Ranging across job categories-from showrunner to make-up artist to location manager-this collection features voices of labor from Los Angeles, Atlanta, Prague, and Vancouver. Together they show how abstract concepts like conglomeration, financialization, and globalization are crucial tools for understanding contemporary Hollywood and for reflecting more generally on changes and challenges in the screen media workplace and our culture at large.